Answered

In Algebra

y = 2 - - 3 ; two minuses make a plus y = 2 + 3 y = 50

Answered

How do you not know this? y = 3. y^3 - y = y(y^2-1) = y(y+1)(y-1) = 3*4*2 = 24. I apologize, for the person who first answered this question is only aware of h…is own skills at math, and is unaware that not everyone understands very advanced math, but he is correct, that is the answer. (MORE)

Answered

Lets say Y=1, when Y goes up 1, x goes up 5 times that amount (5). So if Y=1, y goes up 1 and x goes right 5.

Answered

In Algebra

y equals 8x is a straight line pasing through the origin (0,0) and having a gradient (slope) of 8 (i.e. gradient = "change in y" divided by "change in x" )

Answered

The answer is 25. 5 x 25=125 Think about money. 125 cents = 5 quarters 1 quarter = 25 cents 5 x 25 = 125

Answered

y=3x is a direct variation in that y varies directly with x by a factor of 3. Any linear equation (a polynomial of degree 1, which is a polynomial equation with a highest expo…nent of 1), is a direct variation of y to x by some constant, and this constant is simply the coefficient of the "x" term. Other examples: y=(1/2)x is a direct variation, and the constant of variation is 1/2 y=-9x is a direct variation, and the constant of variation is -9 (MORE)

Answered

In Science

range of y=sin(2x) is [-1;1] and in generally when is y=sin(k*x) (k=....-1,0,1....) range is always [-1;1] and the period is w=(2pi)/k

Answered

In Algebra

It depends on what the question was. Solve 4x - 4 = y for x, you get (y + 4)/4 = x.

Answered

In Science

125 + 125 + 125 + 125 + 125 + 125 = 125 * 6 = (100 * 6) + (20 * 6) + (5 * 6) = 600 + 120 + 30 = 600 + 100 + 20 + 30 = 700 + 50 = 750

Answered

In Algebra

So we have a statement that 3x + y = 7x = 2y. Can we find some values for x and y that will satisfy the statement? Suppose the statement is true, then we have 3x + y = 7x,… which yields y = 4x. or 3x + y = 2y, which yields y = 3x. Thus, 4x = 3x, if and only if x = 0, which also yields y = 0. Therefore, the given statement is true only for x = 0 and y = 0. For other values of x and y, it is a false statement. If there are two equations such as 3x + y = 7 and x = 2y, then substitute 2y for x into the first equation. 3(2y) + y = 7 6y + y = 7 7y = 7 y = 1, thus x = 2y = 2(1) = 2. Therefore the solution point is (2, 1), (MORE)